Genotype-Phenotype Relationships and Endocrine Findings in Prader-Willi Syndrome - Costa, Régis Afonso; Ferreira, Igor Ribeiro; Cintra, Hiago Azevedo; Gomes, Leonardo Henrique Ferreira; Guida, Letícia da Cunha (Frontiers in Endocrinology, 2019)
Prader-Willi syndrome (PWS) is a complex imprinting disorder related to genomic errors that inactivate paternally-inherited genes on chromosome 15q11-q13 with severe implications on endocrine, cognitive and neurologic systems, metabolism, and behavior. The absence of expression of one or more genes at the PWS critical region contributes to different phenotypes. There are three molecular mechanisms of occurrence: paternal deletion of the 15q11-q13 region; maternal uniparental disomy 15; or imprinting defects. Although there is a clinical diagnostic consensus criterion, DNA methylation status must be confirmed through genetic testing. The endocrine system can be the most affected in PWS, and growth hormone replacement therapy provides improvement in growth, body composition, and behavioral and physical attributes. A key feature of the syndrome is the hypothalamic dysfunction that may be the basis of several endocrine symptoms. Clinical and molecular complexity in PWS enhances the importance of genetic diagnosis in therapeutic definition and genetic counseling. So far, no single gene mutation has been described to contribute to this genetic disorder or related to any exclusive symptoms. Here we proposed to review individually disrupted genes within the PWS critical region and their reported clinical phenotypes related to the syndrome. While genes such as NDN, MKRN3, MAGEL2, or SNORD115 do not address the full spectrum of PWS symptoms and are less likely to have causal implications in PWS major clinical signs, SNORD116 has emerged as a critical, and possibly, a determinant candidate in PWS, in the recent years. Besides that, the understanding of the biology of the PWS SNORD genes is fairly low at the present. These non-coding RNAs exhibit all the hallmarks of RNA methylation guides and can be incorporated into ribonucleoprotein complexes with possible hypothalamic and endocrine functions. Also, DNA conservation between SNORD sequences across placental mammals strongly suggests that they a functional role as RNA entities on an evolutionary basis. The broad clinical spectrum observed in PWS and the absence of a clear genotype-phenotype specific correlation imply that the numerous genes involved in the syndrome have an additive deleterious effect on different phenotypes when deficiently expressed.